Improving load balance in Wireless Network using Spatial Reusability - Vijayan, Vinodh P; Joseph, Neena; George, Neema; Mary Kurian, Simy (International Journal of Computer Sciences and Engineering, 2025)
The surest route from the supply node to the destination node that guarantees a high cease-to-stop throughput is the principle trouble of routing in multi-hop wireless network. As the surroundings is heterogeneous the issue seems to be a lot complicated, most of the answers cease with local most desirable due to the fact the ones algorithms often fail to make certain an quit to quit throughput. By considering spatial reusability of wireless media, the cease-to-give up throughput in wi-fi multi-hop far flung structures may be stronger hugely. To assist the argument, Spatial-reusability Aware Single-path Routing (SASR) algorithm is proposed and as compared with existing single direction routing protocol. The assessment showed that proposed protocol display full-size improvement in end-to-give up throughput in evaluation with existing protocols.